Penerapan Metode Role Play dalam Pembelajaran Bahasa Inggris: Mendorong Aktivitas Kreatif Siswa di SMK an Naas Binjai Tahun 2021 - Rudi Purwana; Mariana Mariana; Asrul Asrul; Afina Muharani Syaftriani; Ani Rahmadhani Kaban (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2021)
This community service project explores the application of the role play method in English language learning to encourage creative activities among students at SMK An Naas Binjai in 2021. The primary objective is to assess the effectiveness of role play in enhancing students' engagement and creativity during English lessons. A qualitative research methodology was employed, involving classroom observations, interviews, and analysis of students' performances. The findings indicate that the role play method significantly boosts students' motivation, participation, and creative expression. Additionally, it was observed that role play helps in improving language proficiency and interpersonal skills. The implications of this study suggest that incorporating role play into English language curricula can be a valuable strategy for educators aiming to foster a dynamic and interactive learning environment.